Scheduling in multi-wavelength ring-based optical networks-on-chip - Cerutti, Isabella (Archīum Ateneo, 2018)
Synchronous networks-on-chip (NoC) require tailored schedulers achieving low latency, high throughput, and fairness while avoiding packet collisions. Efficient schedulers exist for rearrangeable non-blocking NoC. However, NoCs fabricated in integrated photonics typically suffer a blocking behavior due to the limitations of the switching capabilities in the space and wavelength domains. This paper discusses a scheduler for an integrated optical NoC based on a ring topology and realized with multiple resonating microrings (multi-microring, MMR). Scheduling in MMR architecture consists of the conventional matching sub-problem and the wavelength assignment sub-problem. The paper's contribution is twofold. An iterative parallel wavelength matching (iPWM) algorithm is presented for jointly addressing both sub-problems. iPWM achieves performance similar to a two-step scheduler based on sequential iSLIP and first-fit wavelength assignment, but with a computational complexity lower than and independent of the number of wavelengths. A comprehensive comparison with the two-step scheduler based on the more complex maximum weighted matching algorithm and with an optimal scheduler is also carried out for the case of fixed and tunable transmitters to assess the trade-off between scheduling complexity and performance. In addition, bidirectionality with one or two transceivers per port is proposed as a way to overcome the throughput degradation caused by the blocking behavior. Simulation results indicate that bidirectionality is very effective in improving the throughput and reducing the latency even when using a single transceiver.